Phylogenetic Analysis of Baccaurea Spp. in West Sumatra Using MatK Molecular Markers - Saswita, Helvi Maudy; Syamsuardi, Syamsuardi; Nurainas, Nurainas; Suwardi, Adi Bejo; Taufiq, Ahmad (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Baccaurea is a group of fruit-producing plants found in wild forests. Many of these plant species have not yet explored their potential. The high rate of deforestation in West Sumatra poses a threat of extinction to the genetic resources of the genus Baccaurea before being explored and identified. The research aims to analyze the sequence characters and phylogenetic of Baccaurea found in West Sumatra using the MatK molecular marker. Phylogenetic analysis using the Maximum Likelihood (ML) method in MEGA X application. The results of the analysis of the six species of Baccaurea found that the sequence length ranged from 854-1019bp, the percentage of G+C base composition is 33.4%, the percentage of A+T base composition is 66.6%, the genetic distance range is 0-4% with a conservative character of 484bp and informative characters of 4bp. While the phylogenetic analysis using the ML method grouping the six species of Baccaurea to form a monophyletic clade with a bootstrap value of 100%, all species collected were in the same clade. These results reveal the first time that the MatK sequences from six species Baccaurea native to West Sumatra will be included in NCBI for use by other studies in conducting broader phylogenetic research.